Classifier Spot Count Optimization of Automated Fluorescent Slide Scanning System - Lucian Zastko; Martin Bereta; Jaroslav Timko; Igor Belyaev (Acta Medica Martiniana, 2022)
Purpose: Ionizing radiation induced foci (IRIF) known also as DNA repair foci represent the most sensitive endpoint for assessing DNA double strand breaks (DSB). IRIF are usually visualized and enumerated with the aid of fluorescence microscopy using antibodies to γH2AX and 53BP1. Although several approaches and software packages were developed for the quantification of IRIF, not one of them was commonly accepted and inter-laboratory variability in the outputs was reported. In this study, the sensitization of Metafer software to counting also small appearing IRIF was validated.